Influence of Vibration of Human Activity Upon a Simple Supported Slab with Tuned Mass Damper (TMD) and Fiber Reinforced Rubber (FRR) Absorber. (2017) - Picauly, Fredy; Priyosulistyo, Henricus; Suhendro, Bambang; Triwiyono, Andreas
Abstract: A popular method to reduce vibration of structures for better comfort is by elaborating damping systems. Tuned mass damper (TMD) is a simple passive system device to control the dynamic amplitude response of the structure due to external vibration excitations. The simple passive device consists of a mass and a spring attached on the structure where the frequency is then tuned in the range of a certain fundamental frequency of the structure. The advantages of this device are reliable, efficient and a low cost of maintenance. This study focused on the performance of a simple tuned mass damper (TMD) with a damping device that was made of fiber reinforced rubber (FRR) attached on the TMD system. The FRR was clamped between the moving mass of the TMD and the structure. This research studied the effectiveness of the FRR on a simple supported slab structure. The result shows that the performance of the TMD with FRR is effective enough to reduce the amplitude response of the slab structure. This research also shows that the FRR on the TMD increases the damping ratio of the slab from 1.21% (without TMD), 2.03% (with TMD), and 2.56% (with TMD+FRR), furthermore when foot step applied on the slab, the maximum acceleration decreases from 0.201 g to 0.081 g.